Public Service Motivation, User Orientation, Affective Commitment, and Job Performance: An Exploratory Analysis on Police Investigator - Rio Adhikara; Novi Indah Earlyanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
As in any public institutions, police organizations are unique with their own characteristics. Previous studies showed that there were varied results which differed from the general assumption regarding the relationships between public service motivation (PSM), user orientation, affective commitment, and job performance among police investigators. Due to the importance of prior findings, our current study examines their underlying reasons and practical implications. We focus on two specific police investigators task: receiving crime report and conducting investigative interviews, both were analyzed in South Tangerang Police Criminal Investigation Division (CID). The PSM, user orientation, and afffective commitment relationship to performance may thus be more complex in police organization as discussed.